1991
DOI: 10.1071/sr9910339
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine persistence and toxicity in two irrigated soils of Australia

Abstract: The persistence of atrazine in two contrasting irrigated soils from the Riverine Plain of south-eastern Australia was measured in the laboratory at three constant temperatures. Particularly at lower temperatures atrazine was more persistent, by an order of magnitude, than reported for soils overseas; but in two successive field experiments, encompassing both surface and incorporated applications of atrazine in the heavier soil, residues measured after about 7 months were within the range expected from the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 18 publications
3
29
0
Order By: Relevance
“…Environmental factors can greatly influence the degradation rate of chemical compounds in soil, the most important being moisture, pH, organic carbon content, and pesticide formulation. Garcia-Valcarcel and Tadeo 9) reported that degradation rates increased with soil moisture content for hexazinone and simazine, which is in agreement with the results of Walker and Blacklow 10) for atrazine and simazine and those of Bowmer 11) for atrazine; therefore, we maintained constant soil moisture. Pfaender and Alexander 12) reported that the numbers of microorganisms potentially able to cometabolize Dichloro Diphenyl Trichloro ethane (DDT) were high in raw sewage as a result of the addition of glucose and diphenylmethane.…”
Section: Degradation Of Pretilachlor and Esprocarb In Soilsupporting
confidence: 89%
“…Environmental factors can greatly influence the degradation rate of chemical compounds in soil, the most important being moisture, pH, organic carbon content, and pesticide formulation. Garcia-Valcarcel and Tadeo 9) reported that degradation rates increased with soil moisture content for hexazinone and simazine, which is in agreement with the results of Walker and Blacklow 10) for atrazine and simazine and those of Bowmer 11) for atrazine; therefore, we maintained constant soil moisture. Pfaender and Alexander 12) reported that the numbers of microorganisms potentially able to cometabolize Dichloro Diphenyl Trichloro ethane (DDT) were high in raw sewage as a result of the addition of glucose and diphenylmethane.…”
Section: Degradation Of Pretilachlor and Esprocarb In Soilsupporting
confidence: 89%
“…However, in a non-irrigated alluvial soil Persicani et al (1996) reported that almost 60% of the atrazine remained in the soil 1 month after application. As reported by Bowmer (1991), the convective movement of evaporating water is expected to increase the accumulation of herbicides at the soil surface, and to enhance the volatilization of the compounds. Other processes that can contribute to the rapid degradation of surface-applied chemicals include photochemical degradation.…”
Section: Following the Subsequent Irrigations [Figs 5(b) And 5(c)]mentioning
confidence: 93%
“…Volatilization of atrazine might have played an important role for this rapid decrease of atrazine in the soil because no irrigation or rain occurred during this initial period. Kearney et al (1964) (cited by Bowmer, 1991) reported substantial volatilization from most soil surfaces, up to 35% loss occurring in 72 h at 353C. Also, Tasli et al (1996) indicated that volatilization reached 15% of the a.i.…”
Section: Plant Development and Yieldmentioning
confidence: 93%
See 1 more Smart Citation
“…This sequestration results in a reduced bioavailability of contaminants to bacteria (Nam et al 1998) and higher organisms such as plants (Bowmer 1991). From a microbial perspective, soils containing an aged contamination can be considered oligotrophic (Wick et al 2003) and harsh environments for microbes to proliferate.…”
mentioning
confidence: 99%